Sentiment Analysis Of Public Comments On Licensing Services Seeks To Use The Naive Bayes Algorithm With Genetic Selection Algorithm - Patue, Abdulatif; Sidik, Guruh Fajar; Affandy, Affandy; Ismail, Abdul Rahman (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The Investment and One-Stop Integrated Service Office is the Licensing Service service to support an area in terms of business potential and investment value. Presenting MSME Business Actors and Young Entrepreneurs. As time goes by, Licensing Services in the Region, especially PTSP, must know what are the constraints and problems faced by business actors in terms of business services and products issued by the Service. Naïve Bayes is the most common algorithm that we encounter in several libraries. Therefore, this research will discuss the level of accuracy of this algorithm. Then additional selection of Genetic Algorithm features was carried out to increase the accuracy of the Naïve Bayes method. The Naive Bayes Algorithm method with Genetic Algorithm selection is superior compared to only using the Naive Bayes method. This is proven by the acquisition of 83.17% accuracy, 86.38% Precision, and 83.05% recall